Risk sharing in quasi-public-welfare water conservancy (PPP) public-private participation projects: an integrated application of Shapley value and utility theory - Liu, Dawei; Liu, Liang; Tan, Xin (Frontiers in Earth Science, 2023)
Quasi-public water conservancy PPP(Public-private participation) projects are closely related to people's livelihoods and involve multiple participating stakeholders. Previous research on risk sharing in such projects has primarily focused on qualitative analysis of risk factors. Due to self-interest considerations, the collaborating parties tend to deflect and transfer risks to each other as much as possible in the risk sharing process. Additionally, some quantitative analysis methods have been predominantly based on a unilateral perspective. Therefore, the present study proposed a new model, which is based on the Shapley Value and the Utility Theory, encompassing a comprehensive analysis of multiple factors such as the proportion of capital contribution, bargaining position, risk management capabilities, and risk-taking willingness of heterogeneous subjects. Firstly, the relationship between the risk losses of different stakeholders and their corresponding value scales and utility attributes is comprehensively analysed, and the transformation characteristics and links of their risk preferences on spatial and temporal scales are summarised. Secondly, The utility values of heterogeneous subjects are employed as quantitative indicators to evaluate utility, leading to the construction of a comprehensive utility objective function for these subjects.Finally, The Shapley Value is then applied to modify the risk-sharing ratio based on the Utility Theory. The research results show that the risk sharing ratio obtained by single use of shapley value theory or utility theory will be biased toward one side, while the result calculated by using the combination of the two methods is 57.35% for the government to share the risk ratio, and 42.65% for the social capital side, which is a more balanced result. The proposed model enriches the risk management method and theory of quasi public welfare water conservancy PPP projects.